WF SS-OCTA for detecting diabetic retinopathy and evaluating the effect of photocoagulation on posterior vitreous detachment - Gong, Yi; Hu, Liying; Wang, Linni; Shao, Yan; Li, Xiaorong (Frontiers in Endocrinology, 2022)
Purpose This study aimed to assess the clinical usefulness of widefield swept source optical coherence tomography angiography (WF SS-OCTA) for detecting microvasculature lesions in diabetic retinopathy (DR) by comparing it with ultra-widefield fluorescein angiography (UWFFA) and to investigate the effect of panretinal photocoagulation (PRP) on posterior vitreous detachment (PVD) status. Methods Patients with severe non-proliferative DR (NPDR) or proliferative DR (PDR) who were initially treated with PRP were enrolled. They underwent WF SS-OCTA with a 12×12-mm scan pattern of five visual fixations at baseline and at least a 3-month follow-up after PRP treatment. Patients with no contraindications underwent imaging with UWFFA within a week. Images were evaluated using two methods for the areas of the visible field of view (FOV), non-perfusion area (NPA), presence of neovascularization of the disc (NVD), neovascularization elsewhere (NVE), and PVD status. Results In total, 44 eyes of 28 patients with DR that were initially treated with PRP were analyzed. The FOV of the UWFFA was significantly wider than that of the WF SS-OCTA. The quantitative measurement of the NPAs was consistent between the two methods. NPAs more than 5DA outside the panoramic OCTA imaging area were detected in 1 eye with NPDR (8.3%) and in 10 eyes with PDR (47.8%). WF SS-OCTA had high detection rates for NVDs and NVEs, with a low rate of false positives. After PRP treatment, no eyes indicated progression in the PVD stages around the macula, optical disc, or NVEs at the short follow-up. Conclusion WF SS-OCTA is clinically useful for evaluating NPAs and neovascularization in DR. PRP treatment does not induce PVD development in the short term.